Simulation and analysis of wind energy potential for turbine systems in Pekanbaru-Indonesia based on MATLAB Simulink - Pranata, Nicholas; Saputri, Fahmy Rinanda (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The widespread use of electricity today, which is primarily generated from fossil fuels, results in significant environmental consequences due to excessive consumption. Renewable energy has been proposed as a solution to mitigate this issue. In Indonesia, particularly in Pekanbaru City, the demand for electricity currently exceeds the supply. However, this region has substantial potential for renewable energy sources. This study presents the modeling and analysis of wind energy, specifically wind turbine systems, using MATLAB Simulink. The methodology involves identifying existing problems, collecting technical data relevant to Pekanbaru and turbine components, and designing the turbine system within MATLAB Simulink. The results of this system indicate a mechanical power output of 1,191 watts, along with a calculated torque of 48.63 Nm. These findings suggest that the system is suitable for small-scale electricity needs. Further research and considerations are necessary to optimize the design and application of turbine systems for sustainable energy production. By improving the efficiency and scalability of wind energy systems, Indonesia can better address its energy deficit while reducing the environmental impacts associated with fossil fuel consumption.